Hubungan Faktor Perilaku Ibu dan Sanitasi Lingkungan Dengan Kejadian Stunting Pada Batita Usia 6-24 Bulan Di Wilayah Kerja Puskesmas Anggeraja Kabupaten Enrekang - Haidah, Nur; Indraswari, Ni Luh Astri; Juherah, Juherah; Murni, Murni (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Stunting is a chronic nutritional problem that can provide an illustration of growth failure that accumulates before and after birth caused by insufficient nutrition.The type of research is Observational Analytical with a Case Control approach which studies the relationship between exposure and disease by comparing case groups and control groups based on their exposure status. The total number of samples was 184 samples.The results of the research were analyzed using the Chi Square statistical test. The results obtained showed that there was a significant relationship between the Behavioral Factors obtained p=0.001 (p<0.05), the Environmental Sanitation results obtained p=0.001 (p < 0.05), and Personal Hygiene. results were obtained p=0.000 (p <0.05) regarding the incidence of stunting. There is a significant relationship between behavioral factors, environmental sanitation and personal hygiene with the incidence of stunting in toddlers aged 6-24 months in the Anggeraja Health Center Working Area, Enrekang Regency. It is recommended for the community, especially mothers, to participate in health services, and process waste properly, such as separating organic and inorganic waste. For community health centers, it is hoped that sanitarian workers will provide education regarding clean water sources, waste management, healthy latrines and waste processing to the community. Keywords: Stunting incidence; environmental sanitation; personal hygiene; maternal behavioral factors